2019
DOI: 10.1002/med.21627
|View full text |Cite
|
Sign up to set email alerts
|

Repurposing approved drugs on the pathway to novel therapies

Abstract: The time and cost of developing new drugs have led many groups to limit their search for therapeutics to compounds that have previously been approved for human use. Many “repurposed” drugs, such as derivatives of thalidomide, antibiotics, and antivirals have had clinical success in treatment areas well beyond their original approved use. These include applications in treating antibiotic‐resistant organisms, viruses, cancers and to prevent burn scarring. The major theoretical justification for reusing approved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(43 citation statements)
references
References 177 publications
0
36
0
2
Order By: Relevance
“…Targeting multiple tumour driving pathways by combinations of targeted drugs applied concurrently or in a specific order may increase the efficacy of treatment by circumventing mechanisms of primary or acquired resistance [34]. Expanding molecular pathology by multiomics technologies to identify tumour drivers and conducting high-throughput functional in vitro screens in cells carrying the same lesions might lead to new combination therapies and offer opportunities for drug repurposing [35].…”
Section: Development Of New Therapiesmentioning
confidence: 99%
“…Targeting multiple tumour driving pathways by combinations of targeted drugs applied concurrently or in a specific order may increase the efficacy of treatment by circumventing mechanisms of primary or acquired resistance [34]. Expanding molecular pathology by multiomics technologies to identify tumour drivers and conducting high-throughput functional in vitro screens in cells carrying the same lesions might lead to new combination therapies and offer opportunities for drug repurposing [35].…”
Section: Development Of New Therapiesmentioning
confidence: 99%
“…De novo drug discovery, usually performed in the pharmaceutical industry, is an expensive and long process. Drug repurposing approaches have been used across a broad spectrum of diseases [108], where many "repurposed" drugs, such as antibiotics, antivirals, and kinase inhibitors, have had clinical success in treatment areas beyond their originally intended use. In a recent study, certain kinase inhibitors, including an inhibitor of PDK1, were able to function as an adjuvant in colistin-resistant bacteria, potentiating the antimicrobial effect in Gram-negative and Gram-positive bacteria [109].…”
Section: Ligand Repurposing Approachesmentioning
confidence: 99%
“…Epidemiological studies revealed a significant increase in the incidence of autoimmune and inflammatory diseases during the last two decades [1]. Accordingly, the total number of patients taking immunosuppressive drugs has been continuously increasing [2]. Long-term administration of immunosuppressive medications is inevitably associated with increased risk of infection and malignancy due to the sustained suppression of anti-microbial and anti-tumor immunity [3].…”
Section: Introductionmentioning
confidence: 99%